Perovskite materials in energy storage and conversion - Zhu, L.; Ran, R.; Tadé, Moses; Wang, Wei; Shao, Zongping (John Wiley & Sons, Ltd, 2016)
In this review, the recent progress in the application of an important category of materials, i.e. ABO3 perovskite-type compounds in the fields of energy storage and conversion, is reviewed. Four main areas, as materials for oxygen transporting membrane toward the application in oxy-fuel combustion, as key material for solid oxide fuel cells for efficient power generation from fuels, as room-temperature electrocatalysts for oxygen reduction reaction and oxygen evolution reaction, and as material for solar cells for solar energy harvest, are referred. Our past efforts in these research areas are emphasized. Some prospects about the future development in the application of perovskite materials in energy storage and conversion is proposed.